Urban planning in Ukraine from the 19th to the early 20th century: integration of science and state management - Tverytnykova, Olena; Gutnyk, Maryna; Heinemann, Manfred (Національний технічний університет "Харківський політехнічний інститут", 2024)
The research is dedicated to analyzing the process of urbanization, particularly the formation and development of cities in northeastern Ukraine at the end of the 19th and beginning of the 20th cen. Special attention is given to the city of Kharkiv and the activities of its mayor, Oleksandr Kostiantynovych Pohorelko (1848–1912). The importance of urban studies as a key direction of humanities research that determines the development of the nation, community, and state is justified. The main tasks faced by the city during that period, such as the municipalization of the economy and the expansion of the city’s rights to private property objects, are highlighted. The role of scientists and researchers, including D. I. Bahalii and M. F. Sumtsov, in promoting the modernization of the city through active participation in municipal authorities is discussed. As a result of the research, significant contributions of O. K. Pohorelko and his colleagues to the development and improvement of Kharkiv at the end of the 19th cen. are identified. The conclusions of the research emphasize the importance of combining scientific potential and civic activism for the implementation of infrastructure development projects in the city.

Дослідження присвячено аналізу процесу урбанізації, зокрема становленню та розвитку міст у північно- східній Україні кін. ХІХ – поч. ХХ ст. Особлива увага приділяється місту Харкову та діяльності його мерії в особі Олександра Костянтиновича Погорелка (1848–1912 рр.). Обґрунтовується важливість урбаністики як ключового напрямку досліджень гуманітарної науки, що визначає розвиток нації, громади та держави. Зазначаються основні завдання, з якими стикалося місто в той період, такі як муніципалізація господарства та розширення прав міста на об’єкти приватної власності. Висвітлено роль вчених та дослідників, зокрема Д. І. Багалія та М. Ф. Сумцова, у сприянні модернізації міста через активну участь у міських органах влади. У результаті дослідження виявлено значний внесок О. К. Погорелка та його співробітників у розвиток та благоустрій Харкова наприкінці ХІХ ст. Висновки дослідження підкреслюють важливість об’єднання наукового потенціалу та громадської активності для реалізації проєктів інфраструктурного розвитку міста.
Урбаністика в Україні ХІХ – початку ХХ ст.: конгломерація науки і державного управління
Keywords: history of science; biographistics; Kharkiv region; local history; Kharkiv Technological Institute; O. K. Pohorelko; історія науки; біографістика; Харківщина; краєзнавство; Харківський технологічний інститут; О. К. Погорєлко